Input and output grammar instruction in tutorial CALL with a complex grammatical structure. (20th January 2015) - Unknown
Abstract : Conceptual replication within a computer-assisted language learning (CALL) environment provides an understanding of the generalizability of second language acquisition (SLA) research (Porte, 2013; Smith & Schulze, 2013). The present study replicates Collentine (1998a), a classroom-based experiment framed within a larger discussion on the relative benefits of input- and output based instruction. Collentine (1998a) compared the benefits of Processing Instruction (VanPatten, 2004) and output-based instruction, both of which elevated the Spanish subjunctive's communicative value. The results showed that input- or output-oriented instruction informed by how learners process grammatical information can affect the acquisition of complex grammatical phenomena. This conceptual replication not only seeks to corroborate the original study's findings in a new learning context. It also tests the finding's generalizability to a tutorial CALL environment built on 3D simulations and emerging web-app technologies. The participants were foreign-language learners of Spanish in a classroom-based curriculum (N = 50). The results indicate that, in the classroom and in a CALL environment, both input- and output-oriented approaches can promote the acquisition of a complex grammatical structure if practice is meaningful (informed by psycholinguistic processing principles) and deliberate, and if feedback is provided.